2017
DOI: 10.1007/s12253-016-0180-4
|View full text |Cite
|
Sign up to set email alerts
|

Is the Genetic Background of Co-Stimulatory CD28/CTLA-4 Pathway the Risk Factor for Prostate Cancer?

Abstract: The impairment of immunological surveillance caused by aberrant T cell activation can lead to an inadequate anti-tumor response. Therefore, deregulation in co-stimulatory pathway might be associated with cancer susceptibility. Here we undertook a prospective study to investigate whether genetic variations in gene encoding molecule CD28 and CTLA-4 playing pivotal role in regulating adoptive immune response can influence susceptibility to prostate cancer. Single nucleotide polymorphisms (SNPs) in CTLA-4 and CD28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The literature search found 788 documents with 132 studies were excluded after duplicates were removed, and 591 studies were excluded after reviewing the retrieved literature’s titles and abstracts. The full text of 65 remaining citations was screened, and finally 19 studies including 11 811 patients were included in this meta-analysis [9,12–15,1831]. The flow chart of the meta-analysis is represented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search found 788 documents with 132 studies were excluded after duplicates were removed, and 591 studies were excluded after reviewing the retrieved literature’s titles and abstracts. The full text of 65 remaining citations was screened, and finally 19 studies including 11 811 patients were included in this meta-analysis [9,12–15,1831]. The flow chart of the meta-analysis is represented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The basic information and quality evaluation (NOS) results included in the study are shown in Table 1. The included studies looked at cancer patients in Asia (n=6) [9,12,13,21,29,30] and Caucasians (n=13) [14,15,18–20,22–28,31]. In addition, in terms of cancer types, leukemia (n=2) [12,26], breast cancer (n=3) [9,13,15], colorectal cancer (n=3) [20,27,30)], cervical cancer (n=4) [2123,28], and other cancers (prostate cancer, gastric cancer, renal cell carcinoma, non-small-cell lung cancer, melanoma, myeloma, lymphoma) were included in studies [4,9,14,18,25,29,31].…”
Section: Resultsmentioning
confidence: 99%
“…These researchers reported that the CTLA-4c.49A>G and CTLA-4g.319C>T SNPs might be considered as low risk susceptibility locus for PCa. 22 The limitation of the study is it cannot find the serum PSA level of control group.…”
Section: Discussionmentioning
confidence: 96%
“…In another study by Karabon et al, 22 SNPs in CTLA-4 and CD28 genes were genotyped in 301 prostate cancer (PCa) patients and 301 controls. These researchers revealed that the frequency of alleles, and genotypes in the CTLA-4 and CD28 genes did not significantly differ between the PCa patients and the controls.…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed overrepresentation of the carriers of the CTLA-4c.49*A allele and the carriers of the CTLA-4c.-319*T allele in patients as compared to controls. Moreover, the individuals possessing both susceptibility alleles CTLA-4c.49*A and CTLA-4c.-319*T had 1.78-fold increased risk of PC than individuals with protective G/G and C/C genotypes, respectively ( 138 ).…”
Section: Cytotoxic T Lymphocyte-associated Antigen-4mentioning
confidence: 99%